Data Encryption and Anonymization Techniques for Enhanced Information System Security and Privacy - Arief Budi Pratomo; Sabil Mokodenseho; Adit Mohammad Aziz (Westscience Press, 2023)
The rapid evolution of digital technology has ushered in a new era of data-driven information systems, bringing both unprecedented convenience and complex challenges to the forefront. This research delves into the realm of data encryption and anonymization techniques to enhance the security and privacy of information systems. The study encompasses a comprehensive exploration of diverse encryption and anonymization methods, evaluating their effectiveness through qualitative and quantitative analysis. A bibliometric analysis, facilitated by VOSviewer, unveils influential authors, research trends, and collaborative networks in the field. The research sheds light on the practical implications of encryption and anonymization techniques through real-world case studies and offers insights into the multidimensional landscape of information system security and user privacy.